The photophysics of nitrocarbazoles studied by using spectroscopic, photoacoustic and luminescence techniques - Mesaros, Mariana (2003)
The photophysical behaviour of 1-nitrocarbazol and 3-nitrocarbazol in different organic solvents has been studied by using spectroscopic, luminescence and photoacoustic techniques. Absorption spectra and triplet state transient spectra were recorded and formation quantum yields and lifetimes determined. Phosphorescence emission at 77 K and laser induced luminescence in acetonitrile solution at 298 K for the nitrocarbazoles were studied. Results are discussed in terms of the optimized structure of 1-nitrocarbazole and 3-nitrocarbazole and compared with that of carbazole. The nitro group attached to the carbazole moiety induces important changes in the photophysical behavior of those compounds.